SMART TRAFFIC CONTROL BARRICADE SYSTEM - Malipatil, Ashwini R; Somasundaram, Dr.K.; M, Ashwini; C Y, Divyashree; N, Kusuma (The journal of contemporary issues in business and government, 2021)
At present traffic management is a big challenge and plays a vital role in moving the vehicles from one corner of the city to the other. This system not only controls the traffic signals but also it reduces violating traffic rules and accidents. Here when the red light signal is ON there will be a servomotor which pops up barricade from ground level. It applies one special condition in the road by placing a barricade before the zebra crossing which will stop the vehicles when the signal red light is ON. The barricade will automatically pops up on the vehicle stopping mark, when the signal leaves it pops down to the ground. For ambulance, it is having a special feature that there will be an RFID tag which can sense about its arrival. For this reason the RFID reader is fixed to road. During the red signal, when the ambulance needs to pass at that time RFID reads the tag and changes red light to green light in traffic signal through GSM where RFID reader card number is stored in control system. So the barricade will pop down to ground and the other three ways are stopped with red signal light so that the ambulance can easily pass through the way by these one can save someone’s life. This project work is carried out by using IOT technology.